Control corruption and innovation: Empirical evidence from upper middle income countries - Nafis Dwi Kartiko (Integritas: Jurnal Antikorupsi, 2025)
This study analyzes the effect of corruption control on innovation in Upper Middle Income Countries (UMIC). Using panel data from 54 UMIC countries for the period 2014-2022 with 486 observations, this study applies Ordinary Least Squares (OLS) regression to identify the relationship between variables. The results show that corruption control has a negative and significant impact on innovation in the overall sample, suggesting a transition effect that initially slows innovation due to increased compliance costs and bureaucratic complexity. However, in countries with a high number of patent applications, corruption control increases attractiveness for foreign investors, creating a conducive environment for research collaboration and technology transfer. Whereas, in countries with high tax revenue, anti-corruption policies reduce the flexibility of fiscal incentives that previously supported innovation. Therefore, corruption control policies need to be balanced with strategies that support the innovation ecosystem to ensure sustainable innovation growth and enhance global competitiveness.